THE APPLICATION OF THE KING’S SCIENCE AND LOCAL WISDOM FOR DEVELOPING LEARNING INNOVATIONS OF PRIMARY SCHOOL STUDENTS THROUGH PARTICIPATION AND MENTORSHIP - Wiwanthamongkon, Karanphon; Pumklom , Mitparnee; Hasdisawi, Krittanan; Sukchaona, Photjanee; Jangjit , Sureewan; Nukaew , Pornchai; Satpreetrai, Supalak (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The objectives of this research were to: 1) study and synthesize approaches to collaboratively developing learning innovations through participation and academic mentoring, 2) jointly develop learning innovations, 3) examine the results of collaborative implementation of learning innovations, and 4) evaluate and extract lessons learned from the collaborative implementation of such innovations. The target schools included 17 primary schools, involving school administrators and teachers from Grades 1–6 who participated in the collaborative development process. The research findings revealed that: 1) the approach to collaborative development of learning innovations was based on the analysis and application of research results, integrating the King’s Philosophy to enhance the quality of education. The schools expressed a need for development in reading and writing due to the challenges posed by the COVID-19 pandemic. 2) The outcomes of the co-development of learning innovations were categorized as follows: 2.1) The innovation in educational administration, both in terms of development and implementation, was at a moderate level of quality, 2.2) innovations for enhancing teaching and learning in reading and writing were of high quality, 2.3) information technology systems were of good quality, and 2.4 assessment and evaluation innovations were also of good quality. 3) The outcomes of collaborative implementation of learning innovations were as follows: 3.1) school administrators utilized administrative innovations at a moderate level on average, 3.2) teachers applied instructional innovations for reading and writing at a high level on average, 3.3) users of the information technology system expressed a high level of satisfaction on average, and 3.4) schools had assessment innovations that included a test bank for students at all grade levels. 4) The evaluation and lesson-learning process indicated that the innovation implementation system and mechanisms were appropriate for school development. ...